Church, Culture, and Their Dimensional Interaction - Dean Frederick Sieberhagen (LPPM STT Baptis Kalvari, 2022)
Culture is a term that is commonly used to describe the actual world that people live in. In the existence of the church, it has had to struggle to interact with culture. Jesus who lived in the Hebrew culture became familiar with this culture and also interacted with other cultures. How Jesus uses culture to proclaim His message needs to be observed. Whether Christ opposes culture or uses culture is interesting to consider. Out of this, there are approaches that can be applied as the church relates to culture. In the end, the church can position itself so that it can affect the culture with God’s Kingdom or have God’s Kingdom diluted in the society as the church is affected by the world.